2012
DOI: 10.1111/ene.12018
|View full text |Cite
|
Sign up to set email alerts
|

Overuse of paracetamol caffeine aspirin powders affects cerebral glucose metabolism in chronic migraine patients

Abstract: Overusing PCA powders affects regional brain glucose metabolism in CM. Increased metabolism in the right insula may be associated with recurrently overusing of PCA powders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Since neural activity is tightly coupled to energy consumption, brain metabolic rate would provide a useful surrogate marker of brain activity. Unfortunately, the vast majority of PET studies of caffeine only measured relative but not absolute values of metabolic rate of glucose, due to the absence of arterial sampling data (Di et al, 2013; Park et al, 2014; Specterman et al, 2005). Thus, the effect of caffeine ingestion on absolute metabolic rate could not be addressed in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since neural activity is tightly coupled to energy consumption, brain metabolic rate would provide a useful surrogate marker of brain activity. Unfortunately, the vast majority of PET studies of caffeine only measured relative but not absolute values of metabolic rate of glucose, due to the absence of arterial sampling data (Di et al, 2013; Park et al, 2014; Specterman et al, 2005). Thus, the effect of caffeine ingestion on absolute metabolic rate could not be addressed in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that posterior regions may have elevated neural activity due to caffeine use. For example, a study of chronic caffeine overuse on brain migraine patients reported increased glucose metabolism in middle temporal gyrus (Di et al, 2013). Griffeth et al used calibrated fMRI methods and showed a 20% increase in CMRO 2 in the visual cortex (Griffeth et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted from Hashmi and others (2012) with permission. (D) Pharmacotherapy: Using 18 F-FDG PET measurements, a significant increase in right insular metabolism has been reported in patients with chronic migraine (CM) and analgesic overuse (AO) compared to both patients with CM without AO and healthy controls ((from Di and others 2013), with permission).…”
Section: Anatomical Aspects Of the Insulamentioning
confidence: 99%
“…This suggests that complete abstinence of caffeine, like abrupt discontinuation of analgesics for those with MOH headaches [ 84 ], may be beneficial to those suffering from migraines [ 83 ]. Furthermore, overuse of APAP/caffeine/ASA has been shown to affect regional brain glucose metabolism in patients with chronic migraine [ 85 ].…”
Section: Reviewmentioning
confidence: 99%